Lateralized Connectivity between Globus Pallidus and Motor Cortex is Associated with Freezing of Gait in Parkinson's Disease. (1st September 2020) - Miranda-Domínguez, Óscar; Ragothaman, Anjanibhargavi; Hermosillo, Robert; Feczko, Eric; Morris, Rosie; Carlson-Kuhta, Patricia; Nutt, John G.; Mancini, Martina; Fair, Damien; Horak, Fay B.
Graphical abstract: Highlights: Freezing of gait is associated with altered functional connectivity between the left pallidus and left somatosensory cortex. Freezing of gait is also associated with negative functional connectivity in the default and vestibular networks. Altered connectivity was a strong and significant predictor of freezing of gait severity. Participants were matched on age, disease severity, cognitive status, and levodopa medication. Findings highlight the importance of lateralized motor loops and multisensory integration in the pathology of freezing. Abstract: Freezing of gait (FoG) is a brief, episodic absence or marked reduction of forward progression of the feet, despite the intention to walk, that is common in people with Parkinson's disease (PD). We hypothesized that not only motor, but higher level cognitive and attention areas may be impaired in freezers. In this study, we aimed to characterize differences in cortical and subcortical functional connectivity specific to FoG. We examined resting state neuroimaging and objective measures of FoG severity and gait from 103 individuals (28 PD + FoG, 36 PD − FoG and 39 healthy controls). Inertial sensors were used to quantify freezing severity and gait. Groups with and without FoG were matched on age, disease severity, cognitive status, and levodopa medication. MRI data was processed using surface-based registration. High-quality imaging data were used to characterize differences in connectivity specific to FoG using a pre-defined set of Regions of Interest (ROIs) and validated using whole-brain connectivity analysis. Associations between functional connectivity and objective measures of FoG were determined via predictive modeling using hold-out cross validation. We found that connectivity between the left globus pallidus (GP) and left somatosensory cortex and between two brain areas in the default and insular/vestibular networks exhibited significant differences specific to FoG and were also strong and significant predictors of FoG severity. Our findings suggest that the interplay among motor, default and vestibular areas of the left cortex are critical in the pathology of FoG.